PERLINDUNGAN HUKUM BIDANG KESEHATAN KERJA BAGI PEKERJA WANITA PADA PACTO LTD TOUR AND TRAVEL DI SANUR KOTA DENPASAR - Rufina Sinuhaji, Ledi; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
This papper titled “Legal Protection of Workers Against Occupational Health Division of Women In Pacto Ltd Tour And Travel in Sanur, Denpasar ". Pacto Ltd Tour And Travel is a company engaged in the field of travel services firm centered in Jakarta, and has employed 400 staff across the Pacto Ltd Tour And Travel. As a company that provides employment, Pacto Ltd Tour And Travel must have a working standards in accordance with Law No. 13 on Labour. In obtaining the necessary data the authors use empirical research to conduct research directly to the Pacto Ltd Tour And Travel. The purpose of this paper is to understand the application of the labor that affect the implementation of occupational health, relating to working time, work breaks, menstruation leave, and maternity leave for women workers at a travel company Pacto Ltd Tour and Travel in Sanur, Denpasar.
Keywords: Protection, Occupional Health, Working Woman